2023
DOI: 10.3390/ijms24065333
|View full text |Cite
|
Sign up to set email alerts
|

Activation of TLRs Triggers GLP-1 Secretion in Mice

Abstract: The gastrointestinal tract constitutes a large interface with the inner body and is a crucial barrier against gut microbiota and other pathogens. As soon as this barrier is damaged, pathogen-associated molecular patterns (PAMPs) are recognized by immune system receptors, including toll-like receptors (TLRs). Glucagon-like peptide 1 (GLP-1) is an incretin that was originally involved in glucose metabolism and recently shown to be rapidly and strongly induced by luminal lipopolysaccharides (LPS) through TLR4 act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Lijuan Wang's [132] experiments also support the idea that LPS affect plasma GLP-1 content via toll-like receptor 4 and that GLP-1 content may reflect intestinal damage to some extent. New research has recently suggested that microbially induced GLP-1 production is not only mediated by LPS and TLR4 but that the activation of other toll-like receptors also leads to increased GLP-1 production [133]. Kahles' [115] study found that LPS dose-and time-dependently increased total serum GLP-1 concentrations in mice, reducing insulin secretion and blood glucose under inflammatory conditions.…”
Section: Glpmentioning
confidence: 99%
“…Lijuan Wang's [132] experiments also support the idea that LPS affect plasma GLP-1 content via toll-like receptor 4 and that GLP-1 content may reflect intestinal damage to some extent. New research has recently suggested that microbially induced GLP-1 production is not only mediated by LPS and TLR4 but that the activation of other toll-like receptors also leads to increased GLP-1 production [133]. Kahles' [115] study found that LPS dose-and time-dependently increased total serum GLP-1 concentrations in mice, reducing insulin secretion and blood glucose under inflammatory conditions.…”
Section: Glpmentioning
confidence: 99%